Exploring the social without a separate domain for religion: on actor-network theory and religion - Mika Lassander; Peik Ingman (Scripta Instituti Donneriani Aboensis, 2012)
In post-secular societies—after secularisation—it may increasingly be the case that the connecting and structuring of religious matter is done outsidedesignated religious sites and without appointed religious experts. The centres of calculation have changed and so the connections between these are different. The former ways of translation and ordering are transforming into new ones. By exiting the designated sites religious matter has found new freedom with the new associations and inventions in the processes of translation. Less control leads to more heterogeneous agencies and facilitates the mobility of religious materials. This less controlled mobility of religious actants can also produce an apparent increase of religious matter, but this does not necessarily mean the return of religion. In any case, this increased plurality combined with increased mobility calls for perspectives which can recognise novelty, andnot just in comparison with previous states of affairs. Actor-network theory (ANT) is about tracing the webs of associations between myriad actants whose collective actions produce what we call ‘society’. Dismissing the notion of ‘the social’ as a kind of ‘stuff ’, ANT insists that sociology should focus on the interactional processes—the circulation of ‘the social’ among human and non-human actants—collectively assembling emerging states of affairs.